2015
DOI: 10.14393/bj-v31n4a2015-26122
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of lettuce fertilized with controlled-release nitrogen fertilizer and urea

Abstract: ABSTRACT:Lettuce demands high levels of nitrogen, which appears in the soil in forms that present a complex dynamic, making it difficult to apply nitrogen-based fertilizers. One way to improve the efficiency of nitrogen absorption is to use controlled-release nitrogen fertilizers, which aim to maintain nitrogen in forms that are less susceptible to loss. The objective of this study was to evaluate the effect of two sources of N (urea and coated urea -slow-release N) in two management systems (fertilizer only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…For Yeshiwas et al (2018), high rates of nitrogen application adversely affect product quality, increasing nitrate accumulation in leaves that directly influence human health. Pedrinho et al (2015) concluded that the use of protected (encapsulated) urea in Americana lettuce crop did not increase yield when compared to managed urea in planting, on the other hand, the use of managed urea in planting and in cover; showed higher productivity than the protected urea source. As in Ferreira et al (2019a) when approaching in their research that the production components in corn crop were enhanced by the presence of Polyblen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Yeshiwas et al (2018), high rates of nitrogen application adversely affect product quality, increasing nitrate accumulation in leaves that directly influence human health. Pedrinho et al (2015) concluded that the use of protected (encapsulated) urea in Americana lettuce crop did not increase yield when compared to managed urea in planting, on the other hand, the use of managed urea in planting and in cover; showed higher productivity than the protected urea source. As in Ferreira et al (2019a) when approaching in their research that the production components in corn crop were enhanced by the presence of Polyblen.…”
Section: Resultsmentioning
confidence: 99%
“…The application of fertilizers with adequate doses of N in lettuce crop is a convenient strategy, since its basically leaf composition provides high response to the availability of this mineral (Melo et al 2018). The efficiency of N can be increased by using controlled release N-based fertilizers, which aim to keep the element in less loss-prone forms (Pedrinho et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2012) et al in the maize crop and Silva Junior et al (2016) in the production of fruits of Caryca papya L., verified the effect of slow release nitrogen, when compared to urea. Pedrinho et al (2015) working with rapid cycle crop, as the lettuce, and with slow release and traditional urea, found no differences in productivity among the studied sources. Veçozzi et al (2018) using N sources with urea and urea coated with polymers, in the irrigated rice crop, found no effect among the sources.…”
Section: Introductionmentioning
confidence: 82%
“…Todavia, relatos de teores abaixo daqueles tidos como referência mesmo com produtividade adequada são, relativamente, frequentes. Oliveira et al (2010), por exemplo, ao analisarem amostras foliares de alface (cv. Regina 2000) em cultivo orgânico, encontraram valores entre 27,6 a 29,3 g kg -1 N. Por sua vez, Resende et al (2012) avaliaram os efeitos de diferentes doses de N e Mo em alface americana (cv.…”
Section: Discussionunclassified
“…No entanto, esta fonte apresenta uma desvantagem em relação às demais, pois o N deste fertilizante pode ser perdido por volatilização na forma de NH3 quando não incorporado adequadamente ao solo (SILVA et al, 2012). Para reduzir ou eliminar estas desvantagens a ureia pode ser revestida com uma ou mais camadas de polímeros, as quais tem a finalidade de reduzir a velocidade de dissolução do fertilizante e, logo, a liberação do nutriente (PEDRINHO et al, 2015).…”
Section: Introductionunclassified